2013
DOI: 10.5194/gmd-6-2087-2013
|View full text |Cite
|
Sign up to set email alerts
|

Correction of approximation errors with Random Forests applied to modelling of cloud droplet formation

Abstract: Abstract. In atmospheric models, due to their computational time or resource limitations, physical processes have to be simulated using reduced (i.e. simplified) models. The use of a reduced model, however, induces errors to the simulation results. These errors are referred to as approximation errors. In this paper, we propose a novel approach to correct these approximation errors. We model the approximation error as an additive noise process in the simulation model and employ the Random Forest (RF) regression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…The probable reason why the LFRF method performs so well, outperforming even GPE, is that it is supported with an embedded dependency, the linear model LF. This is in line with Lipponen et al (2013Lipponen et al ( , 2018 where they showed that including a dependency (= correcting a rough empirical model with random forest) improved results compared to a pure random forest learning method. LF is the least accurate method in all simulation sets, except in SALSA day where it outperforms the GPE only slightly.…”
Section: Parameterisation Intercomparisonsupporting
confidence: 85%
See 2 more Smart Citations
“…The probable reason why the LFRF method performs so well, outperforming even GPE, is that it is supported with an embedded dependency, the linear model LF. This is in line with Lipponen et al (2013Lipponen et al ( , 2018 where they showed that including a dependency (= correcting a rough empirical model with random forest) improved results compared to a pure random forest learning method. LF is the least accurate method in all simulation sets, except in SALSA day where it outperforms the GPE only slightly.…”
Section: Parameterisation Intercomparisonsupporting
confidence: 85%
“…The approach used in this study is similar to the approximation error correction method introduced in Lipponen et al (2013) and Lipponen et al (2018). In Lipponen et al (2018), it was shown that predicting and correcting the approximation error of the output of an approximative model often leads to more accurate results than directly predicting the model output.…”
Section: Linear Fit Improved With Random Forest (Lfrf)mentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we train the machine learning model for post-process correction of the approximation error in the result of the conventional retrieval algorithm. While the postprocess correction approach is new to satellite retrievals, it has been found to perform better and produce more stable and accurate results than a fully learned approach in generation of surrogate simulation models (Lipponen et al, 2013(Lipponen et al, , 2018 and in medical imaging, where many of the inverse imaging problems are mathematically highly similar to the satellite retrieval problems; see for example Hamilton et al (2019). The key advantages of the new modelenforced post-process correction approach are (1) the improved accuracy over the existing data products and existing fully learned satellite data approaches and (2) the possibility to post-process-correct existing (past) satellite data products with no need for full re-processing of the enormous satellite datasets.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, we train the machine learning model for post-process correction of the approximation error in the result of the conventional retrieval algorithm. While the post-process correction approach is new to satellite retrievals, it has been found to perform better and produce more stable and accurate results than a fully learned approach in generation of surrogate simulation models (Lipponen et al, 2013(Lipponen et al, , 2018 and in medical imaging, where many of the inverse imaging problems are mathematically highly similar to the satellite retrieval problems, see for example Hamilton et al (2019). The key advantages of the new model enforced post-process correction approach are 1) the improved accuracy over the existing data products and existing fully learned satellite data approaches, and 2) the possibility to post-process correct existing (past) satellite data products with no need for full re-processing of the enormous satellite datasets.…”
mentioning
confidence: 99%